2015
DOI: 10.1016/j.slsci.2015.02.003
|View full text |Cite
|
Sign up to set email alerts
|

The validity of Actiwatch2 and SenseWear armband compared against polysomnography at different ambient temperature conditions

Abstract: There were no validation studies on portable sleep devices under different ambient temperature, thus this study evaluated the validity of wrist Actiwatch2 (AW2) or SenseWear armband (SWA) against polysomnography (PSG) in different ambient temperatures. Nine healthy young participants (6 males, aged 23.3±4.1 y) underwent nine nights of study at ambient temperature of 17 °C, 22 °C and 29 °C in random order, after an adaptation night. They wore the AW2 and SWA while being monitored for PSG simultaneously. A linea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
71
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(71 citation statements)
references
References 18 publications
0
71
0
Order By: Relevance
“…Shin et al reported that using the medium threshold for Actiwatch2 provided minimal bias for SOL, TST, and SE but overestimated WASO at different ambient temperatures in a small group of healthy young adults. 3 Meltzer et al reported that the medium setting in healthy children provided results most similar to PSG. 6 Similarly, Ward et al reported that in healthy children as well as those with juvenile arthritis and asthma, the medium threshold setting provided the least biased results.…”
Section: Differences In Sleep Parameter Agreement By Threshold Settingmentioning
confidence: 97%
See 3 more Smart Citations
“…Shin et al reported that using the medium threshold for Actiwatch2 provided minimal bias for SOL, TST, and SE but overestimated WASO at different ambient temperatures in a small group of healthy young adults. 3 Meltzer et al reported that the medium setting in healthy children provided results most similar to PSG. 6 Similarly, Ward et al reported that in healthy children as well as those with juvenile arthritis and asthma, the medium threshold setting provided the least biased results.…”
Section: Differences In Sleep Parameter Agreement By Threshold Settingmentioning
confidence: 97%
“…In a group of healthy adults, the Actiwatch2 underestimated TST at various ambient temperatures (7.1 to 17.6 minutes) and overestimated WASO (7.1 to 12.4 minutes) when using the medium setting. 3 Using the Actiwatch64 (Philips Respironics, Oregon, United States) device, an earlier Actiwatch model no longer on the market, Cellini and colleagues reported the low and medium threshold settings underestimated TST (by 1.1 to 4.7 minutes) whereas the high threshold produced results similar to the PSG. 1 These differences from the current findings may reflect that sleep is different in young adults with T1DM but also could be due to several factors, including differences in actigraphy devices and timing of sleep period (naps versus overnight).…”
Section: Differences In Sleep Parameter Agreement By Threshold Settingmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, actigraphy was offered as an elective procedure and also depending on the availability of Actiwatches. Actigraphy data were obtained using the Actiwatch2 34,35 (Philips Respironics; software: Actiware 6.02). We examined MDTA, which was calculated using total activity counts divided by total active time in minutes of Tuesday, Wednesday, and Thursday, during the first week of the study.…”
Section: Actigraphy Data Analysismentioning
confidence: 99%